2017
DOI: 10.1186/s12891-017-1663-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of electrical stimulation in the management of avascular necrosis of the femoral head in adults: a systematic review

Abstract: BackgroundAvascular necrosis of the femoral head causes significant morbidity and occurs in up to 20,000 people per year. A variety of nonoperative and operative measures have been trialled however a definitive treatment algorithm is yet to be established. Young adults in many cases have undergone multiple surgical procedures in their lifetime with increasing risks of complications. Less invasive techniques may help reduce the number of operations required and positively influence the natural history of the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 20 publications
(56 reference statements)
0
25
0
1
Order By: Relevance
“…[ 1 , 2 ] Increased incidence of ONFH was reported over the past decade, and an estimated of 20,000 to 30,000 and 150,000 to 200,000 new cases of ONFH were respectively presented annually in the United States and China. [ 3 , 4 ] Moreover, a total of 8.12 million ONFH patients in China remains a challenge to surgeons. [ 5 ] As the main form of ONFH, steroid-associated osteonecrosis of the femoral head (SONFH) is one of the most common and severe complications following corticosteroid treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 , 2 ] Increased incidence of ONFH was reported over the past decade, and an estimated of 20,000 to 30,000 and 150,000 to 200,000 new cases of ONFH were respectively presented annually in the United States and China. [ 3 , 4 ] Moreover, a total of 8.12 million ONFH patients in China remains a challenge to surgeons. [ 5 ] As the main form of ONFH, steroid-associated osteonecrosis of the femoral head (SONFH) is one of the most common and severe complications following corticosteroid treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Previous study has reported that electrical stimulation can be used to treat a variety of pain conditions, especially for NMES. [ 18 – 24 ] However, few studies focused on using electrical stimulation to treat patients with NFH. As far as we know, no study has explored the effectiveness of NMES for the treatment of NFH.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 – 18 ] These options include medications, surgical treatments, and other alternative interventions, such as Chinese herbal medicine, acupuncture, rest, extracorporeal shock wave therapy, and electrical stimulation. [ 11 – 18 ] However, these options still suffer from limited efficacy, and even very server adverse events (AEs) and complications. Thus, alternative candidates with few AEs are urgently needed to treat this condition.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of ONFH has increased over the past decade. It is estimated that 20000 to 30000 new patients are diagnosed with ONFH annually in the United States and 150000 to 200000 new cases in China 3 , 4 . Moreover, the treatment of adult ONFH, with 8.12 million patients in China, remains a challenge to surgeons 5 .…”
Section: Introductionmentioning
confidence: 99%